ОБ ИЗВЕСТНОМ И НЕИЗВЕСТНОМ ЭЛЕКТРОСТАТИЧЕСКОМ ПОЛЕ, И ЕГО ИНФОРМАЦИОННОЙ СОСТАВЛЯЮЩЕЙ (Experimental biology, 2015)
Electrostatic charges form micro and macro structures which have an effect on ecosystem, and also on behavior of the person and animals.
Keywords: micro and macro structures; person and animal